Seismic vulnerability assessment of historical masonry structural systems - Asteris, Panagiotis G.; Chronopoulos, M.P.; Chrysostomou, Christis; Varum, H.; Plevris, V.; Kyriakides, Nicholas; Silva, V. (My University, 2014)
Masonry structures are complex systems that require a thorough and detailed knowledge and information regarding their behavior under seismic loading. Appropriate modeling of a masonry structure is a prerequisite for a reliable earthquake resistant design or assessment. However, modeling a real structure to a robust quantitative (mathematical) representation is a very difficult, complex and computationally demanding task. This paper presents a methodology for earthquake resistant design or assessment of masonry structural systems. The entire process is illustrated using case studies from historical masonry structures in the European area. In particular, the applicability of the proposed method is checked via analyses of existing masonry buildings in three countries, namely Greece, Portugal and Cyprus, with different seismicity levels, influencing the risk impacting the masonry structures. Useful conclusions are drawn regarding the effectiveness of the intervention techniques used for the reduction of the vulnerability of the case-study structures, through the comparison of the results obtained.
Keywords: Historical structures; Fragility curves; Masonry; Retrofitting; Structural assessment; Structural modeling